Improving information transfer between heterogeneous CAD packages - Awaluddin Mohamed Shaharoun; Raj Sreerangam; See, Chen Yong; Juhari Ab. Razak; Muhammad Rabiul Alam (Skudai : Universiti Teknologi Malaysia, 1997)
57